A prospective trial of structured treatment interruptions in human immunodeficiency virus infection. - Fagard, C; Oxenius, A; Günthard, H; Garcia, F; Le Braz, M; Mestre, G; Battegay, M; Furrer, H; Vernazza, P; Bernasconi, E; Telenti, A; Weber, R; et al. (2003)
BACKGROUND: According to the "autovaccination hypothesis," reexposure to human immunodeficiency virus (HIV) during treatment interruptions may stimulate the HIV-specific immune response and lead to low viremia after withdrawal of highly active antiretroviral treatment (HAART). Many patients who started HAART earlier in their disease course than is currently recommended would like to discontinue, but it is unknown whether it is safe to do so. OBJECTIVES: To determine whether repeated treatment interruptions of HAART (1) stimulated the cytotoxic HIV-specific immune response and whether such stimulation correlated with low viremia off treatment, and (2) were safe with respect to clinical complications, development of viral resistance, and decline in CD4 cell counts. DESIGN: Interventional study with before-after comparison. SETTING: Outpatient clinics of university hospitals in Switzerland and Spain. PATIENTS: A total of 133 patients receiving HAART, with a median CD4 cell count of 740/ microL, and whose viral load had been undetectable for a median of 21 months. INTERVENTIONS: HAART was interrupted for 2 weeks, restarted, and continued for 8 weeks. After 4 such cycles, treatment was indefinitely suspended 40 weeks after study entry. MAIN OUTCOME MEASURES: HIV-specific cytotoxic T-cell responses were evaluated by interferon gamma enzyme-linked immunospot analysis. The proportion of "responders" (viral load <5000 copies/mL) was measured at weeks 52 and 96. HIV-related diseases and CD4 cell counts were recorded. RESULTS: Seventeen percent of patients (95% confidence interval, 11%-25%) were responders at week 52, and 8% at week 96. Low pre-HAART viral load and lack of rebound during weeks 0 to 40 predicted response. HIV-specific CD8+ T cells increased between week 0 (median, 343 spot-forming cells per million peripheral blood lymphocytes [SFC/106 PBL]) and week 52 (median, 1930 SFC/106 PBL), but there was an inverse correlation between response and the number of spot-forming cells. Eighty-five (64%) of 133 patients stopped therapy for at least 12 weeks, and 55 (41%) for at least 56 weeks. The median CD4 cell count decreased from 792/ microL to 615/ microL during the first 12 weeks without treatment, but stabilized thereafter. One patient (0.75%) developed drug resistance necessitating salvage treatment. There were no AIDS-related clinical complications. CONCLUSIONS: Results of this study do not favor the autovaccination hypothesis. Treatment interruptions did not provoke clinical complications, and there was little drug resistance. Comparative trials will have to show what benefit, if any, is associated with intermittent, as opposed to continuous treatment.